The Paradigm of Science Integration in The Development of Higher Education - Yanti, Herina; Charles, Charles (Ahlussunnah: Journal of Islamic Education, 2025)
The paradigm of combining science and Islam is an effort to unite modern knowledge with Islamic religious values philosophically and epistemologically. Until now, higher education in the Islamic world has often separated religious knowledge from general knowledge, which has led to a separation in academic thinking and practice. This study aims to explore the philosophical basis for combining science and Islam, as well as its impact on the development of higher education. Using a qualitative method based on literature review, this study finds that combining science and Islam is not only theoretical but can also be applied in real life. This is done by considering revelation as a source of values and science as a tool for advancing civilization. This paradigm is capable of creating a comprehensive higher education model that focuses on the development of knowledge with ethics and is able to respond to global challenges without losing Islamic identity. Thus, the integration of science and Islam has great potential as a basis for developing curricula, learning strategies, and research directions in Islamic universities.